Corrosion behavior of TC18 titanium alloy with different initial microstructures in salt spray - Hui Li; Baogang Wang; Junsheng Yang; Xiaopeng Liu; Jianyi Zhang; Ruiqi Ye (Journal of Materials Research and Technology)
This study investigated the corrosion behavior of TC18 titanium alloy with different initial microstructures in neutral salt spray environment by microstructural analysis, corrosion composition analysis, and electrochemical test in 3.5 wt% NaCl solution. In addition, the pitting mechanism of TC18 titanium alloy in salt spray corrosion was analyzed. Through SEM and Sensofar Neox 3D morphology observation, it was found that alloys with different microstructural morphologies exhibited different levels of corrosion resistance during the salt spray corrosion process, and that the pitting pit of TC18 titanium alloy with different initial microstructure tended to remain stable with increasing salt spray treatment time. The local dissolution of the passivation film was identified as the primary corrosion mechanism during the salt spray process of TC18 titanium alloy with different initial microstructures, as determined by XPS and EDS compositional analysis. The pitting corrosion resistance of TC18 titanium alloy can be effectively enhanced by its initial equiaxed microstructure, which has a smaller grain size, as evidenced by microstructural analysis, electrochemical impedance spectroscopy (EIS) results, and complementary evaluation analysis of Tafel polarization curves. Finally, a comprehensive discussion of the salt spray corrosion mechanism of TC18 titanium alloy is provided. This comprehensive study provides critical insights into the durability of marine equipment and the efficacy of preventive measures to mitigate the occurrence of pitting corrosion.